A Study on Congruence between Classical Nyaya Sutras and Modern Theories of Knowledge. (October 2015) - Pandey, Jatin; Singh, Manjari
Knowledge is an asset that can make or break organizations. Its importance has been duly asserted in the Western management thought as well as in the Indian classical philosophical thought. The present study takes a hermeneutical approach by reviewing the Western literature related to knowledge and then trying to find congruence with the Indian philosophy of Nyaya Sutras. Nyaya is a branch of Indian philosophical thought; these thoughts were written in the form of verses called the sutras. We draw from the modern knowledge management literature and compare and contrast it with selected verses of Nyaya Sutras. We find a high level of similarity between the two and discuss offerings from Nyaya Sutras that can be adopted by the modern knowledge management domain. The key aspects of our work have been consolidated in a conceptual model for knowledge management which will provide useful insights to modern management practices.